2019
DOI: 10.3390/met9010045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempering Temperature on Microstructures and Wear Behavior of a 500 HB Grade Wear-Resistant Steel

Abstract: The microstructure and wear behavior of a 500 Brinell hardness (HB) grade wear-resistant steel tempered at different temperatures were investigated in this study. The tempering microstructures and wear surface morphologies were studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The relationship between mechanical properties and wear resistance was analyzed. The microstructure of the steel mainly consisted of tempered martensite and ferrite. Tempered troosite was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Based on Brinell's hardness to temperature linkage diagram, the strength of steel can be reduced when the temperature is more than 300°C. 14 During the production process, steel which is the constituent component of the kiln shell has a temperature range between 200°C to 250°C. 14 Therefore, heat can become dangerous when the temperature increases from 100°C to1800°C in the burning zone without control.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Brinell's hardness to temperature linkage diagram, the strength of steel can be reduced when the temperature is more than 300°C. 14 During the production process, steel which is the constituent component of the kiln shell has a temperature range between 200°C to 250°C. 14 Therefore, heat can become dangerous when the temperature increases from 100°C to1800°C in the burning zone without control.…”
Section: Discussionmentioning
confidence: 99%
“…This might lead into a more severe impacts requiring higher toughness properties. A study by Wen et al [14] showed that the improved impact toughness by tempering might provide better wear resistance when steels are tested in severe impact loading conditions. Therefore, the balance of mechanical properties and wear resistance is essential when choosing the suitable steel for a given application.…”
Section: Cross-sections Of the Worn Surfacesmentioning
confidence: 99%
“…Thus, the effect of tempering on the wear resistance is of great interest. Some examples of studies conducted on the topic can be found by Trevisiol et al [13], Wen et al [14], and Wei et al [15]. However, the wear tests have been typically done using pin-on-disc or another similar very simplified device.…”
Section: Introductionmentioning
confidence: 99%
“…In the manufacturing process of wear-resistant steels, quenching and tempering can effectively control the comprehensive properties such as wear resistance and hardness, which has been widely studied [13][14][15][16]. Abbasi et al compared the properties of low alloy steels after multiple tempering [17].…”
Section: Introductionmentioning
confidence: 99%